Project Management - AD2248 - 202201 - Raicovi Nazal, Giancarlo Martin (2022)
Course Overview: Numerous surveys suggest that employers increasingly recognize project management as one of the most important skills that business students should possess. Whether or not you plan to become a project manager, you will inevitably work on various project teams in different capacities, or your own projects. Understanding basic principles of project management, and knowing how to use the concepts, tools and methods of this booming field, can significantly increase the chance that you become successful with these endeavors. In fact, the methods and principles that you learn in this class can be readily applied to your other classes, the whole MS in MIS program, your work, and even your personal life. As will soon become clear, "common sense" is essential in project management, but this field is much more than that: Effective management of projects requires "applying common sense with uncommon discipline" (Textbook #1, page 3). This course will take you through a typical process of managing projects, including organizing, planning, and performing projects; and will present to you a scientific, systematic approach to project management. Prerequisite Requirements: No prior management information systems knowledge is assumed in this course. However students are required to download and install Microsoft Project 2016 before class starts, or as soon as possible at the beginning of the course. Instructions are provided in the D2L course space.